SCREENING OF SOME MEDICINAL PLANTS FOR ANTIBACTERIAL ACTIVITY AGAINST CONJUNCTIVITIS - S. Meher; I. Ali; A. Sami; M. Ismail; N. Naheed; S. A. Khan; V. U. Ahmad (Journal of Animal and Plant Sciences, 2017)
Antibiotic resistance is a persistently emerging problem all over the world. The constituents of therapeutic plant extracts play a key role in antimicrobial drug discovery. Extracts of 36 medicinal plant species of Pakistan origin that belong to 33 genera and 24 families were tested against the bacterial strains Staphylococcus aureus and Pseudomonas aeruginosa. In addition the extracts of 23 plant species classified in 21 genera and 17 families were assessed against the bacterial clinical isolates (S. aureus, P. aeruginosa), using the agar well diffusion method. As a result, 10 plant extracts exhibited different properties against the specific bacterial strains. Some plant extracts were also tested against the clinical P. aeruginosa and S. aureus isolates. Among the tested samples, Haleej, Anaar and Kali Mirch exhibited the highest relative percentage inhibition against S. aureus while Kala Zeera, Abhal and Khobani showed the highest inhibition against P. aeruginosa. In addition Anar exhibited the highest inhibition against the clinical S. aureus isolate while Pista followed by Zeera showed the highest inhibition against the clinical P. aeruginosa isolate. The results obtained in our present study might help explain the ethnobotanical importance of the screened plant species for the treatment of conjunctivitis.
Keywords: Plant extracts-Antibacterial activity-Clinical isolates-Conjunctivitis